EXPERIMENTAL STUDY ON FRACTURE TOUGHNESS OF MULTILAYER WELD JOINT BASED ON MICROSTRUCTURE - WU HaiLi; JIA GuoQing; AN ChunXiang (Jixie qiangdu)
Quasistatic fracture toughness tests have done on SAW multilayer weld joint of Ni Cr Mo V scaled steel. The test result shows that the dispersion of fracture toughness J of SAW multilayer weld joint was large. J-R fracture resistance curve was fit and critical Jc（ 25）with pop-in behavior were calculated according to the different of brittle and ductile fracture phenomenon.The crack initiation parts of brittle and ductile fracture of multilayer welding specimens were analyzed respectively by scanning electron microscopy. There is a great relation between the multilayer weld fracture toughness and the position of pre-crack tip in the weld joints. Analysis and research have been done about the cause of formation of different microstructures of multilayer and effects on fracture toughness properties. It is known that the complex organization of bold columnar crystals, incomplete recrystallized coarse grain and incomplete recrystallized fine grain alternating exists is the essential cause of the large dispersion of fracture toughness.